Physiological, neuromuscular and perceived exertion responses in badminton games - Phomsoupha, M.; Ibrahime, S.; Heugas, A.; Laffaye, G. (International Journal of Racket Sports Science, 2019)
The purpose of this study was to characterise the physiological, neuromuscular and perceived exertion variables during a badminton match and to assess the influence of these variables on the characteristics of the game. Each variable was measured before, every ten minutes, and ten and twenty minutes after a badminton game. Using a lactate device, a heart rate monitor, an accelerometric system, a dynamometer, a camera and a Borg scale, twelve games between elite players were analysed. An increase was found in the heart rate, blood lactate and in the recovery time, while a decrease was found in the power output of the lower and upper limb joints and shot frequency.These results suggest the capability of the players to preserve a high intensity of performance for as long as possible despite general fatigue. The fatigue induced by changes in physiological variables is affected more by the intensity of the stroke rather than the duration of the rallies. The perceived exertion is thought to be a combination of attentional and neuromuscular fatigue rather than related to changes in metabolites. Consequently, in future studies, researchers and trainers should consider thefatigue state as a meansto increase players` ability.